Assessment on the economic damage of trading households due to urban inundation - Hung, B. V.; Diep, N. N. (Journal of water and climate change, 2022)
Floods impact most of the subjects living and producing in Ho Chi Minh City (HCMC). Trading households are one of the important economic sectors in the economic development of HCMC. This sector contributes greatly to development from GDP to creating jobs and attracting a large workforce cooperating with them such as goods traffic and business services. Because the trading households are of small business scale and very diverse, they are often scattered in residential areas, along roads. They are also adversely affected and suffer economic losses due to inundation, like citizens. The determination of damage level to all objects including trading households is one of the flood management activities and the basis for infrastructure development projects as well as social support policies of the city. Through a direct survey of more than 3,419 trading households and applying the economic loss curve method, this research has established a correlative function for economic losses due to inundation with flood depth and duration. With the correlative function of flood damage for trading households, the district and city's agencies will have a new tool to assess and analyze the damage level of trading households selling in the area.